Mental actions - O'Brien, Lucy, 1964-; Soteriou, Matthew (Oxford : Oxford University Press, 2009)
The twelve specially written essays in this volume investigate the neglected topic of mental action, and show its importance for the metaphysics, epistemology, and phenomenology of mind. The essays investigate what mental actions are, how we are aware of them, and what is the relationship between mental and physical action.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Act (Philosophy); Agent (Philosophy)